Renal Function and Death in Older Women: Which eGFR Formula Should We Use? - Muna T. Canales; Terri Blackwell; Areef Ishani; Brent C. Taylor; Allyson Hart; Rebecca J. Beyth; Kristine E. Ensrud (International Journal of Nephrology)
Background. The Berlin Initiative Study (BIS) eGFR equations were developed specifically for aged populations, but their predictive validity compared to standard formulae is unknown in older women. Methods. In a prospective study of 1289 community-dwelling older women (mean age 79.5 years), we compared the performance of the BIS1 SCr-based equation to the CKD-EPIcr and the BIS2 SCr- and Scysc-based equation to the CKD-EPIcr,cysc to predict cardiovascular and all-cause mortality. Results. Prevalence of specific eGFR category (i.e., ≥75, 60–74, 45–59, and <45) according to eGFR equation was 12.3%, 38.4%, 37.3%, and 12.0% for BIS1; 48.3%, 27.8%, 16.2%, and 7.8% for CKD-EPIcr; 14.1%, 38.6%, 37.6%, and 9.6% for BIS2; and 33.5%, 33.4%, 22.0%, and 11.1% for CKD-EPIcr,cysc, respectively. Over 9±4 years, 667 (51.8%) women died. For each equation, women with eGFR <45 were at increased risk of mortality compared to eGFR ≥75 [adjusted HR (95% CI): BIS1, 1.5 (1.1–2.0); CKD-EPIcr, 1.7 (1.3–2.2); BIS2, 2.0 (1.4–2.8); CKD-EPIcr,cysc, 1.8 (1.4–2.3); p-trend <0.01]. Net reclassification analyses found no material difference in discriminant ability between the BIS and CKD-EPI equations. Results were similar for cardiovascular death. Conclusions. Compared to CKD-EPI, BIS equations identified a greater proportion of older women as having CKD but performed similarly to predict mortality risk. Thus, the BIS equations should not replace CKD-EPI equations to predict risk of death in older women.